Understanding the attributes of the dual oasis effect in an arid region using remote sensing and observational data - Qiang Bie (Taylor & Francis Group, 2020)
Investigating the attributes of the dual oasis effect and oasis–desert interactions is crucial for understanding the climatic and ecological effects of oases. In this study, oasis effect intensity (OEI) was used as an indicator to investigate the factors that contribute to the dual oasis effect. The oasis effect has two attributes: the surface oasis heating effect (OHE) occurred in winter, while the oasis cooling effect (OCE) occurred in the other three seasons, especially in summer. During the day, the OEI of the whole oasis was −12.8°C, −5.2°C, and −4.5°C in summer, spring, and autumn, respectively, which indicated a strong OCE; and OEI was 0.5°C in winter, which indicated a weaker OHE. In arid regions, the OCE dominated most of the time, but the OHE occurred in winter and cannot be ignored. In addition, through statistical analysis and energy balance analysis, high evapotranspiration of the oasis was the main factor leading to the occurrence of OCE in the summer, while low albedo to the occurrence of OHE in winter.